Research and Application of Urban Flood Model in Shenzhen River and Bay Basin - LENG Yubo; LIU Shu; ZHENG Jingwei; ZHANG Yang; LIU Xunping; WANG Zheng (Renmin Zhujiang, 2024)
Affected by the frequent occurrence of heavy rainfall and the high development of urbanization, Shenzhen has carried out urban flood model research and application with the Shenzhen River and Bay Basin as the pilot area to improve the early warning and forecasting and flood control emergency decision-making ability in the event of heavy rainfall and enhance the forward-looking and accurate flood control treatment under heavy rainfall. In this context, this paper collects the topography of the Shenzhen River and Bay basin, pipe network, underlying surface, river network, rainstorm and flood process, and other data. Combined with application scenarios, it builds a rapid flood early warning and dispatch model of hydrology + river channels and a refined urban flood model of hydrology + river channels + pipe network + surface. At present, based on the boundary conditions of rain, water (tide), and construction conditions at different temporal and spatial scales of the basin, the flood model of Shenzhen River and Bay Basin has achieved good application results in the "four pre", flood risk analysis, emergency event analysis, extreme rainstorm analysis and other aspects. This study provides important technical support for the refined management of flood risk in highly urbanized areas.